Pengembangan Media Pembelajaran Multimedia Interaktif Wordwall untuk Percepatan Kemampuan Berhitung Perkalian Siswa Paket A PKBM Al Hasyimi II - Sumilah, Sumilah; Rusmawati, Retno Danu; Harwanto, Harwanto (LP. Ma'arif Janggan Magetan, 2023)
The results of the initial survey found that students' multiplication counting skills and the use of interactive multimedia learning media tools were very low. On the other hand, the ability to count is needed every day, so researchers need to innovate to develop wordwall interactive multimedia learning media to help speed up multiplication arithmetic skills. This type of research is the Borg and Gall Model Development Research. The results of this research product are in the form of manuals for the use of interactive multimedia learning media Wordwall. The target of this research were class 1 package A students at PKBM Al Hasyimi II. The feasibility level of this guide is seen based on the validity of the assessment of material experts, media experts and design experts. The validation results of material experts obtained 94.70%, media experts obtained 84.50%, and design experts 92.50% so that the validation results of 3 experts can be categorized as very good/very feasible. To see the students' responses to wordwall interactive multimedia learning media, trials were carried out in 2 stages, namely small group trials and large group trials. After that conducted interviews and observations of students. The results of the interviews and observations made show that wordwall interactive multimedia learning media can help students learn multiplication.